Awareness Regarding Chronic Kidney Disease Among Adults in a Hospital of Siddharthanagar Municipality - Ghimire, Sulochana; Neupane, Gita; Sah, Chanda (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: Chronic kidney disease (CKD) has been recognized as a leading public health problem worldwide. Early detection and management of the risk factors of CKD is helpful for its prevention and reduction of burden caused by it. This study aimed to find out the awareness regarding chronic kidney disease among adults in a hospital of Siddharthanagar Municipality. MATERIAL AND METHODS: Hospital based descriptive cross-sectional study was used to find out the awareness regarding chronic kidney disease among 165 adults attending Medical out patient department of Universal College of Medical Sciences, Bhairahawa, Rupandehi, Nepal from July 11 to July 25, 2021. Descriptive and inferential statistics were used to assess the awareness level and its association with different socio-demographic variables. RESULTS: The findings of the study showed that 57.6% of respondents had low level of awareness regarding chronic kidney disease. Respondents have high awareness on risk factors of chronic kidney disease whereas respondents have relatively low awareness on meaning and clinical features of chronic kidney disease. CONCLUSION: On the basis of findings, it is concluded that more than half of the respondents have low awareness level regarding chronic kidney disease so an effort should be made to improve the awareness regarding chronic kidney disease for early identification and management of chronic kidney disease.